2020
DOI: 10.1021/acscatal.0c02983
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Influence of Supercritical Carbon Dioxide on the Electrochemical Reduction to Formic Acid Using Carbon-Supported Copper Catalysts

Abstract: The electrocatalytic reduction of carbon dioxide (CO2) by means of renewable energies is widely recognized as a promising approach to establish a sustainable closed carbon cycle economy. However, widespread application is hampered by the inherent difficulty in suppressing the hydrogen evolution reaction and controlling the overall process selectivity. Further critical parameters are the limited solubility of CO2 in many electrolytes and its hindered mass transport to the electrodes. Herein we report on a serie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…Nanoparticles can improve the apparent solubility of poorly soluble substances, but naked nanoparticles readily self‐aggregate 22, 23 . Currently, direct chemical modification or coating additives and carriers onto nano‐sized particles can prevent aggregation, 24, 25 and the latter method is used most frequently.…”
Section: Resultsmentioning
confidence: 99%
“…Nanoparticles can improve the apparent solubility of poorly soluble substances, but naked nanoparticles readily self‐aggregate 22, 23 . Currently, direct chemical modification or coating additives and carriers onto nano‐sized particles can prevent aggregation, 24, 25 and the latter method is used most frequently.…”
Section: Resultsmentioning
confidence: 99%
“…Our group recently showed that under high pressure conditions in supercritical CO 2 , suppression of HER from an FE of 60% to below 8% is possible. The resulting shift in product distribution compared to measurements under ambient conditions led to current efficiencies of up to 66% for the formation of formic acid ( Junge Puring et al., 2020 ).…”
Section: Process Conditionsmentioning
confidence: 99%
“…In addition to adsorbates, local concentrations of key reactants such as H + and CO play a significant role in determining product selectivity in carbon dioxide reduction . For example, in other heterogeneous catalysts, boosting the local concentration of CO by combining a catalyst that is highly active for CO production with a surface with favorable CO binding and C–C bond formation has achieved great success for the production of C 2+ products. , Changing the concentration of reagent by changing solvents (e.g., moving to super critical CO 2 instead of atmospheric concentrations) has also been shown to change selectivity for heterogeneous CO 2 reduction catalysts . Here, the small pores of MOFs provide a unique platform for boosting local concentrations of key reactants or intermediates that may change reactivity or selectivity for a desired reaction.…”
Section: Selectivity and Efficiencymentioning
confidence: 99%